Predicting Word Reading Deficits Using an App-Based Screening Tool at School Entry - Martin Schöfl; Martin Schöfl; Gabriele Steinmair; Daniel Holzinger; Daniel Holzinger; Christoph Weber; Christoph Weber (Frontiers Media S.A., 2022)
BackgroundReading is a crucial competence associated with academic development, mental health, and social adaptation. Reading difficulties are often detected at a late stage, with a possible negative impact on long-term reading development and secondary developmental disadvantages. The first manifestations of reading difficulties can be identified by word reading deficits in first and second grade, paving the way for specific interventions. For widespread implementation, instruments must be easy to use and motivating for children.ObjectivesDevelopment and validation of an economical, well-accepted, and accurate screening tool composed of the domains of phonological information processing, language skills, and non-verbal intelligence in regular school settings.DesignIn 2020, the screening tool was used on a sample of 409 first graders between the second and fifth weeks of school in a one-to-one setting. Additionally, information on parental education and the use of German and/or other languages by the child was collected using a parental questionnaire. A follow-up involving the use of established standardized word reading tests was conducted at the end of the first school year.ResultsA five-variable screening tool consisting of the dimensions of phonological information processing (letter knowledge, rapid naming, and phonological awareness) and linguistic skills (receptive vocabulary and morphosyntax) showed statistical relevance (AUC = 0.78; sensitivity 0.80, specificity 0.74) for predicting word reading problems concerning reading speed (<16th percentile) at the end of first grade, whereas gender, first language, and age of first exposure to the German language did not contribute to the prediction. The instrument was well accepted by the children and screeners and can be administered within an acceptable time frame.ConclusionWord reading deficits at the end of first grade can be predicted by the use of an app-based screening tool at school entry that includes phonological information processing and language skills. Further validation and assessment of empirical feasibility data are needed to support the screening instrument for German orthography.